Deleterious effects of plant cystatins against the banana weevil Cosmopolites sordidus - Kiggundu, Andrew; Muchwezi, Josephine; Van der Vyver, Christell; Viljoen, Altus; Vorster, Juan; Schluter, Urte; Kunert, Karl; Michaud, Dominique (Published in Collaboration with the Entomological Society of America, 2010)
The general potential of plant cystatins for the development of insect-resistant transgenic plants still remains to be established given the natural ability of several insects to compensate for the loss of digestive cysteine protease activities. Here we assessed the potential of cystatins for the development of banana lines resistant to the banana weevil Cosmopolites sordidus, a major pest of banana and plantain in Africa. Protease inhibitory assays were conducted with protein and methylcoumarin (MCA) peptide substrates to measure the inhibitory efficiency of different cystatins in vitro, followed by a diet assay with cystatin-infiltrated banana stem disks to monitor the impact of two plant cystatins, oryzacystatin I (OC-I, or OsCYS1) and papaya cystatin (CpCYS1), on the overall growth rate of weevil larvae. As observed earlier for other Coleoptera, banana weevils produce a variety of proteases for dietary protein digestion, including in particular Z-Phe-Arg-MCA-hydrolyzing (cathepsin L–like) and Z-Arg-Arg-MCA-hydrolyzing (cathepsin B–like) proteases active in mildly acidic conditions. Both enzyme populations were sensitive to the cysteine protease inhibitor E-64 and to different plant cystatins including OsCYS1. In line with the broad inhibitory effects of cystatins, OsCYS1 and CpCYS1 caused an important growth delay in young larvae developing for 10 days in cystatin-infiltrated banana stem disks. These promising results, which illustrate the susceptibility of C. sordidus to plant cystatins, are discussed in the light of recent hypotheses suggesting a key role for cathepsin B–like enzymes as a determinant for resistance or susceptibility to plant cystatins in Coleoptera.